Chitosan- and salicylic acid-mediated enhancement of andrographolide in Andrographis paniculata (Burm.f.) Wall. leaf callus - Patuhai, Aicah; Dewir, Yaser Hassan; Megat Wahab, Puteri Edaroyati; Mohammad Yusoff, Martini; Alsughayyir, Ali; Hakiman, Mansor (Elsevier, 2026)
Andrographis paniculata (Burm.f.) Wall., widely known as the “King of Bitters,” is valued for its medicinal diterpenoid andrographolide. The present study investigated the effects of surface-sterilization treatments, plant-growth regulators (PGRs), and elicitors on callus induction and andrographolide accumulation in A. paniculata leaf explants. Leaf tissues sterilized with 60 % sodium hypochlorite for 1 min achieved 83.33 % survival and 96.67 % aseptic culture. The optimal callus formation occurred on MS medium containing 1.0 mg L−1 2,4-dichlorophenoxyacetic acid (2,4-D) + 0.5 mg L−1 kinetin, giving 96 % callus induction within 8.4 ± 0.0 days, 2.8 ± 0.0 g fresh weight, and 2.2 ± 0.0 cm diameter. Chitosan at 5 mg L−1 produced 100 % survival and markedly enhanced biomass (3.0 ± 0.0 g; 2.5 ± 0.0 cm diameter). High-performance liquid chromatography (HPLC) analysis revealed that 5 mg L−1 chitosan increased andrographolide content to 962.07 ± 0.27 μg g−1 approximately 6.8-fold higher than the control (123.44 ± 0.16 μg g−1). These results establish a reproducible protocol for callogenesis of A. paniculata and demonstrate that elicitation substantially improves callus growth and andrographolide yield, offering a sustainable platform for secondary-metabolite production.